Governments' Payment Discipline : The Macroeconomic Impact of Public Payment Delays and Arrears - Checherita-Westphal, Cristina (IMF Working Papers; Working Paper ;, 2015)
This paper considers the impact of changes in the payment discipline of governments on the private sector. We argue that increased delays in public payments can affect private sector liquidity and profits and hence ultimately economic growth. We test this prediction empirically for European Union countries using two complementary approaches. First, we use annual panel data, including a newly constructed proxy for government arrears. We find that payment delays and to some extent estimated arrears lead to a higher likelihood of bankruptcy, lower profits, and lower economic growth. However, while this approach allows a broad set of variables to be included, it restricts the number of time periods. We therefore complement it with a Bayesian VAR approach on quarterly data for selected countries faced with significant payment delays. We again find that the likelihood of bankruptcies rises when governments increase the average payment period.